Bridging Hebrew and Yiddish: Dvora Baron’s Multilingual Vision in “Ogmat Nefesh” - Emma Avagyan (Religions)
Dvora Baron’s “Ogmat Nefesh” exemplifies the complexities of early 20th-century Jewish multilingualism, offering distinct Hebrew and Yiddish versions of the story to explore intersections of gender, ideology, and identity. This paper draws on theoretical frameworks from Harshav’s concept of the “language of power”, Miron’s notion of “amphibianism”, Even-Zohar’s polysystem theory, and Brenner’s “lingering bilingualism” to examine how Baron’s bilingual authorship shapes her narrative strategies and critiques systemic inequities. Through close readings of key passages, it analyzes how her linguistic choices influence character portrayal, narrative tone, and thematic emphasis across the two versions. Situating “Ogmat Nefesh” within the historical contexts of Eastern European and Palestinian Jewish communities, the study also considers Baron’s engagement with Zionist and diasporic frameworks and her feminist critique of patriarchal structures. Finally, Baron’s personal experiences of exile and literary seclusion further illuminate the interplay between individual circumstances and cultural production in her work. By engaging with secondary scholarship and feminist perspectives, this study highlights Baron’s contributions to early 20th-century feminist writing and her enduring relevance to debates on multilingualism and cultural identity in Jewish literature.